STRENGTHENING THE TAHFIZ STUDY SYSTEM IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0: DIRECTIONS AND CHALLENGES IN MALAYSIA - Muhammad Iqbal Samadi; Dian Widiantari; Azmil Hashim (Universitas Pendidikan Indonesia, 2022)
The high acceptance and response of the public to tahfiz education has provided space for the government to provide various alternatives to tahfiz education through the approval of the Ulama Council to implement the National Policy on Tahfiz Education (DPTN). The main purpose of this research is to see how far the development of tahfiz education and soft skills (KI) among huffaz are. Related to that, the four curriculum modules that will be introduced are Tahfiz Turath, Tahfiz Sains, Tahfiz Dini and Tahfiz Kemahiran. Among the main directions and challenges that need to be faced are the combination of ideas, competitive infrastructure and a strong implementation commitment to ensure that the Tahfiz institution continues to excel on the world stage. In the end, empowerment of the education system and tahfiz studies can produce professional huffaz who have a balance of religious knowledge, secular academics, personality and technology skills simultaneously in developing holistic human capital in the current era of the Industrial Revolution 4.0